Liver lesion conspicuity during real‐time MR‐guided radiofrequency applicator placement using spoiled gradient echo and balanced steady‐state free precession imaging. Issue 2 (29th October 2013) - Rempp, Hansjörg; Loh, Henning; Hoffmann, Rüdiger; Rothgang, Eva; Pan, Li; Claussen, Claus D.; Clasen, Stephan
<x xml:space="preserve">Abstract</x> Purpose To retrospectively evaluate the conspicuity of liver lesions in a fluoroscopic spoiled gradient echo (GRE) and a balanced steady‐state free precession (SSFP) magnetic resonance imaging (MRI) sequence. Materials and Methods In all, 103 patients with hepatocellular carcinomas (HCC) (41) or liver metastases (67) were treated using MR‐guided radiofrequency ablation in a wide‐bore 1.5 T scanner. A multislice real‐time spoiled GRE sequence allowing for a T1 weighting (T1W) and a balanced SSFP sequence allowing for a T2/T1W contrast were used for MR guidance. The contrast‐to‐noise‐ratio (CNR) of the lesions was calculated and lesion conspicuity was assessed retrospectively (easily detectable / difficult to detect / not detectable). Results HCC was easily detectable in 33/52% (GRE/SSFP), difficult to detect in 30/18%, and not detectable in 37/30% of the cases. Mean CNR varied widely (9.1 for GRE vs. 16.4 for SSFP). Liver metastases were easily detectable in 58/41% (GRE/SSFP), difficult to detect in 14/21%, and not detectable in 28/38% of the cases. Mean CNR for liver metastases was 11.5 (GRE) vs. 12.7 (SSFP). Twenty percent of all lesions could not be detected with either of the MR fluoroscopy sequences. Conclusion MR fluoroscopy using GRE and SSFP contrast enabled real‐time detectability of 80% of the liver lesions. J. Magn. Reson. Imaging 2014;40:432–439. © 2013 Wiley Periodicals, Inc.